From the Primacy of Letter to Poslexia: An Itinerary for a Debate on Language, Information and Political Subjectivity - Cataldo-Gonzalez, H; Yuing-Alfaro, T (CENTRO ALTOS ESTUDIOS FILOSOFICOS & CIENCIAS SOCIALES-CENALTES, 2024)
The paper analyzes the subjective profiles in politics within the current communicational scheme. The global world, connectivity and images are elements that invite us to pay attention to how words and information work nowadays. This review takes contributions from Sartori, Serres and Ranciere, among others. Then, the place of the literate as a device of community articulation is discussed. To this end, the thesis of angel Rama is examined: the primacy of the letter implies a social order with a severe impact on political institutionality. Subsequently, the notion of postlexia suggested by Mark Fisher, who affirms the "illiterate" character of the present time, is incorporated. A dialogue is thus constructed in which some of the perspectives involved are deepened. Finally, some questions are suggested as to its effects on political subjectivity. These questions draw on the contributions of Virno, Castillo and Ferraris, among others